Stream connectivity structures fish assemblage beta diversity through turnover and nestedness in tropical tributaries - Akhyar, Ammar; Abdullah, Ahmad Fikri; Hassan, Zafri (Springer Science and Business Media, 2026)
Stream connectivity affects tropical fish communities, but its impact on beta diversity components, turnover (species replacement) and nestedness (species loss or gain), in tributaries remains unclear. We sampled 15 tributary sites in Malaysia’s Pahang River basin during the dry season. Each site was repeatedly sampled for three time culminating 45 site visits altogether. Fish assemblages recovered were assessed using the Sørensen dissimilarity index (βsor) that was partitioned into turnover (βsim) and nestedness (βsne) to assess diversity patterns within the stream network. Species detection rates varied (0.33 to 1.0), with 69% of 45 total species recovered showing moderate detection probability (≤ 0.66). The high proportions of the recovered fish with only moderate and low detection probability highlights the need for replicate surveys to increase detectability in tropical stream networks. Between-sites beta diversity was dominated by species turnover (βsim = 0.056 to 0.520), indicating that differences in assemblage composition among sites were mainly due to species replacement, while nestedness-related species loss played a smaller role (βsne = 0.000 to 0.278). The higher βsim relative to βsne indicates that assemblage differences are structured by environmental gradients, primarily the elevation, reflecting habitat heterogeneity and species sorting or niche differentiation rather than species loss. Overall, the river network supports differential connectivity: well-connected for species replacement processes but more constrained for nested hierarchical structure, with middle reaches playing key integrative roles. Their ecological role, evidenced by the species checklist which shows them hosting a mixture of rheophilic and limnophilic species. The current balance, with turnover dominant and nestedness low, indicates a system where natural assembly processes still prevail for the study basin. Our findings emphasize that effective, basin-wide management must prioritize processes sustaining metacommunity dynamics, as a focus on species richness (alpha diversity) alone overlooks these critical system functions.